Situação clínica, lesional, microbiológica e molecular em 24 equídeos com resultado positivo em testes sorológicos para mormo no estado de Mato Grosso, Brasil - Rocha, Leandro da Silva (2022)
Glanders is a zoonosis caused by the bacterium Burkholderia mallei (B. mallei) that affects mainly solipeds. The disease can manifest as ulcerated lesions on the skin and mucosa, edema in the limbs, progressive weight loss and pyogranulomas in several organs. The lack of vaccination and the impossibility of treatment make glanders an obstacle to the development of equideoculture. The Ministry of Agriculture, Livestock and Supply establishes the mandatory euthanasia of equine reagents in official diagnostic serological tests, however serodiagnosis is difficult because in many cases equines are asymptomatic, which generates conflicts between breeders, veterinarians and animal health defense agencies. This work describes the clinical, morphological and complementary exam findings in 24 equines, from different municipalities in the State of Mato Grosso, which reacted to the Complement Fixation test and were positive in the Western Blotting test for glanders in the years 2015 and 2017. The horses were clinically evaluated, sent for euthanasia and immediately submitted to necropsy. Except for one horse that died spontaneously from intercurrent illness and was necropsied six hours after death. Tissue samples were collected for histological, microbiological and molecular analysis in order to characterize the infection by B. mallei. In 23 horses there were no clinical signs, morphological changes, microbiological isolation or molecular detection that characterized glanders. One asymptomatic case with no lesional alterations showed sequence amplification compatible with B. mallei in PCR. Glanders is a disease subject to the application of animal sanitary defense measures, and the sanitation procedure is supported by serological results.